Evaluating N2O emissions and carbon sequestration in temperate croplands with cover crops: insights from field trials - V. Nasser; R. Dechow; M. Helfrich; A. Meijide; P. S. Rummel; P. S. Rummel; H.-J. Koch; R. Ruser; L. Essich; K. Dittert (SOIL)
Cover crops (CCs) are acclaimed for enhancing the environmental sustainability of agricultural practices by aiding in carbon (C) sequestration and reducing losses of soil mineral nitrogen (SMN) after harvest. Yet, their influence on nitrous oxide (N2O) emissions – a potent greenhouse gas – presents a complex challenge, with findings varying across different studies. This research aimed to elucidate the effects of various winter CCs – winter rye (frost-tolerant grass), saia oat (frost-sensitive grass), and spring vetch (frost-sensitive legume) – compared to a bare fallow control on SMN dynamics, N2O emissions, and C sequestration. These effects were determined by measuring SMN dynamics and N2O emissions in field experiments. The effects of CCs on soil C sequestration over a 50-year period were predicted by soil organic C (SOC) models using measured aboveground and belowground CC biomass. While CCs efficiently lowered SMN levels during their growth, they slightly increased N2O emissions compared to bare fallow. In particular, winter frost events triggered significant emissions from the frost-sensitive varieties. Moreover, residue incorporation and tillage practices were associated with increased N2O emissions in all CC treatments. Winter rye, characterized by its high biomass production and nitrogen (N) uptake, was associated with the highest cumulative N2O emissions, highlighting the influence of biomass management and tillage practices on N cycling and N2O emissions. The CC treatment resulted in a slight increase in direct N2O emissions (4.5±3.0, 2.7±1.4, and 3.1±3.8<mspace width="0.125em" linebreak="nobreak"/>kg<mspace linebreak="nobreak" width="0.125em"/>N2O-N<mspace width="0.125em" linebreak="nobreak"/>ha-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="122pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="e65564e6ffe09ed8f8f419c46bd84065"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-489-2025-ie00001.svg" width="122pt" height="16pt" src="soil-11-489-2025-ie00001.png"/></svg:svg> for rye, oat, and vetch, respectively) compared to the fallow (2.6±1.7<mspace linebreak="nobreak" width="0.125em"/>kg<mspace width="0.125em" linebreak="nobreak"/>N2O-N<mspace linebreak="nobreak" width="0.125em"/>ha-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="122pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="148d1da385bc02e394c04dd3d4223c24"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-489-2025-ie00002.svg" width="122pt" height="16pt" src="soil-11-489-2025-ie00002.png"/></svg:svg>) over the entire trial period (18 months). However, the potential of non-legume CCs to reduce indirect N2O emissions compared to fallow (0.3±0.4 and 0.2±0.1<mspace linebreak="nobreak" width="0.125em"/>kg<mspace linebreak="nobreak" width="0.125em"/>N2O-N<mspace width="0.125em" linebreak="nobreak"/>ha-1<mspace width="0.125em" linebreak="nobreak"/>a-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="140pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="72e7097d5182e0b560823bdc8d1956b5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-489-2025-ie00003.svg" width="140pt" height="16pt" src="soil-11-489-2025-ie00003.png"/></svg:svg> for rye and oat, respectively) and their contribution to C sequestration (120–150 kg<mspace width="0.125em" linebreak="nobreak"/>C<mspace linebreak="nobreak" width="0.125em"/>ha-1<mspace linebreak="nobreak" width="0.125em"/>a-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="65pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="0d5dee1caffb7a62d26638443b1b7069"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-489-2025-ie00004.svg" width="65pt" height="15pt" src="soil-11-489-2025-ie00004.png"/></svg:svg> over a period of 50 years when CCs were grown every fourth year) might partially counterbalance these emissions. Thus, while CCs provide environmental benefits, their net impact on N2O emissions requires further research into optimized CC selection and management strategies tailored to specific site conditions to fully exploit their environmental advantages.